Toxicity of the Delonix elata (L.) Gamble (Caesalpiniaceae) in Leaf - Kilimozhi, D.; Parthasarathy, V. (Asian Journal of Chemistry, 2010)
Delonix elata (family: Caesalpiniaceae) is an indigenous plant for treatment of convulsions, arthritis, measles, piles, chronic bronchitis, rheumatisam and arthritis. Delonix elata was evaluated for its toxicity by the oral route in mice and rat. The effect of acute toxicity was carried out in (72 h) and sub-acute (30 days) treatment of the drug with different dosage on liver and kidney functions and hematological and biochemical parameters were studied. The acute toxicity studies with this drug did not produce mortality at any dose level given (5-2000 mg kg-1 body weight) and up to the dose level of 5000 mg kg-1 did not produce any mortality. No marked adverse alterations were observed in hematological and biochemical parameters during the sub-acute toxicity studies (50, 100, 250 and 500 mg kg-1 body weight). In the sub-acute treatment, the highest dose (500 mg kg-1 body weight) alone showed a moderate increase in the level of plasma urea, uric acid and creatinine. Decreased level of urinary urea, uric acid and creatinine levels were also observed. Histopathological examination of vital organs showed normal architecture suggesting no morphological disturbances.